Tunable THz and Infrared Plasmonic Filters and Switches Based on Circular Graphene Resonator With 90 $^°$ Bending of Output Port - Victor Dmitriev; Geraldo Melo; Wagner Castro (IEEE Photonics Journal)
Two types of novel graphene-based components, namely, filters and electro-optical switches in guided wave configuration are suggested and analysed. The filters differ from the known ones with collinear orientation of the input and output waveguides by geometry and symmetry. The components consist of a circular graphene disk and two nanoribbons oriented at $90^°$ to each other in the plane of the graphene layer. The graphene elements are placed on a dielectric substrate. We show that change in symmetry leads to a drastic change in the properties of the components. The physical principle of the devices is based on the dipole, quadrupole and hexapole resonances in the graphene disk which define stop-band, pass-band and stop-band frequency characteristics, respectively. A combination of stop-band and pass-band filter properties by shifing the electronic Fermi level allows one to design a switch. Numerical simulations show that the suggested components have very small dimensions, good characteristics and provide a dynamic control of their central frequency via electrostatic gating.